6v = 5/8+ 7/8
6v= 12/8
6v=6/4 = 3/2
V= (3/2)/6
V=(3/2) • (1/6)
V= 3/12
V = 1/4
Answer: Capitalism
Step-by-step explanation:
hope it helps
Proof by induction
Base case:
n=1: 1*2*3=6 is obviously divisible by six.
Assumption: For every n>1 n(n+1)(n+2) is divisible by 6.
For n+1:
(n+1)(n+2)(n+3)=
(n(n+1)(n+2)+3(n+1)(n+2))
We have assumed that n(n+1)(n+2) is divisble by 6.
We now only need to prove that 3(n+1)(n+2) is divisible by 6.
If 3(n+1)(n+2) is divisible by 6, then (n+1)(n+2) must be divisible by 2.
The "cool" part about this proof.
Since n is a natural number greater than 1 we can say the following:
If n is an odd number, then n+1 is even, then n+1 is divisible by 2 thus (n+1)(n+2) is divisible by 2,so we have proved what we wanted.
If n is an even number" then n+2 is even, then n+1 is divisible by 2 thus (n+1)(n+2) is divisible by 2,so we have proved what we wanted.
Therefore by using the method of mathematical induction we proved that for every natural number n, n(n+1)(n+2) is divisible by 6. QED.
The answer should be 3.8
You can find this by dividing the total descent by the minutes the descent took
Answer: 6 inches each.
Step-by-step explanation: 24/4 because it is a square it has 4 sides all the same length(please vote me brainliest)!